FLAT SLAB SHEAR WALL INTERACTION FOR MULTISTORIED BUILDING ANALYSIS WHEN STRUCTURE LENGTH IS GREATER THAN WIDTH UNDER SEISMIC FORCES (International Journal of Engineering Sciences & Management Research, 2017)
In recent times there has been a considerable increase in the number of tall buildings, both residential and commercial, and modern trend is towards taller structures. Flat slab is most widely used systems in reinforced concrete construction. Flat-slab building structures possesses main advantages over traditional slab-beam-column structures taking a advantages of reduced floor height, shorter construction time, architectural – functional and economical aspects. But in flat slab building columns are directly provides supports to slab with eliminating beams so there is requirement of provision of shear walls to increase the stiffness of building against lateral forces. Shear wall system are one of the most commonly used lateral load resisting in high rise building. Shear wall has high in plane stiffness and strength. The aim of the present study is to evaluate the behavior of multi-storeyed building of conventional R.C.C. having flat slab with or without shear walls and to analyze the effect of building height and length on the performance under earthquake forces. Also effect of with or without shear wall for flat slab building on seismic behavior with varying thickness and varying position of shear wall are studied. In this work, the effects of seismic forces in zone V on these buildings are also carried out.